Effects of Fiscal Consolidations in Latin America. Issue Volume 66:Issues 4(2018) (December 2018) - Diniz, André
Abstract We use data on structural primary balances for Latin America to estimate effects of fiscal consolidations. Identification relies on a doubly robust estimator that controls for the endogeneity of fiscal policy using inverse probability weighting. Results suggest a negative multiplier on impact, with the economy starting to recover from the second year on and expanding after 5 years. Revenue-based adjustments are more contractionary on impact than expenditure-based adjustments. Among demand components, we find consumption to be generally less responsive to consolidations than investment. Results also depend on the initial levels of debt and taxation. In comparison with OECD evidence, Latin American countries display larger, but stop-and-go consolidations, with state-dependent long-run multipliers.